SRR Slotted Multiband Antenna in Sub 6-GHz for Futuristic Communication - Mishra, Ranjan; Dandotia, Rajeev; Gaurav Mishra, Raj; Kuchhal, Piyush; Kumar Pachauri, Rupendra (EAI Endorsed Transactions on Energy Web, 2020)
Futuristic communication in sub 6-GHz demands a compact antenna with multi-band resonance. This would be necessary to cater to the need in LTE, Wireless Fidelity, and 5G applications. A compact microstrip inverted slotted antenna for the future sub 6 -GHz wireless and mobile applications employs an important role in the present scenario. In this investigation, a slotted antenna especially for multi-band mobile applications in sub 6-GHz is presented. The slotted rectangular patch is matched with a microstrip offset feed line and stub matching. The performance of the single-layer slotted antenna is significantly improved using a slotted SRR structure. The designed antenna shows good reflections co-efficient at 3 GHz and 4 GHz with good return loss. The antenna exhibits impedance bandwidth up to 200 MHz and peak gain up to 4 dBi. It finds its application at the precise frequency for mobile wireless communication in LTE and sub 6-GHz for future 5G applications.